Effect of Management Practices on Soil Nutrient Status of Apple Orchards in Kullu District of Himachal Pradesh - Sharma, Priyanka; Singh, Mohinder; Bhardwaj, S. K. (International Journal of Economic Plants, 2019)
Apple (Malus domestica Borkh) is one of the important fruit crops in Himachal Pradesh. The study was conducted to evaluate the soil nutrient status of apple orchards at different altitudes (Bajaura: 1090m amsl, Seobagh: 1189 m amsl, Naggar: 1880 m amsl and Arsu: 2080m amsl) and with different fertilizer management practices (low input and high input) in Kullu district of Himachal Pradesh during the years 2015 and 2016. In each location, twelve orchards were selected and six to seven trees in each orchard were randomly marked for soil nutrient evaluation. The study revealed maximum average soil pH (6.77) and OC (2.92%) in low input orchards as compared to high input orchards. Soil pH (6.47), electrical conductivity (0.31) and organic carbon (2.49) were found maximum at highest location i.e. Arsu as compared to other locations. High input orchards recorded higher values of soil macronutrients N (330.4 kg ha-1), P (36.64 kg ha-1) and K (287.4 kg ha-1) than low input orchards. Similarly, soil micronutrients Fe, Zn and Cu were also found higher in high input orchards.